Punjab Service Delivery Assessment : A Decision-Making Tool for Transforming Funds into Improved Services - World Bank (World Bank, Islamabad, 2017)
The Punjab province has seen visible and laudable improvements in the quantum of water supply and sanitation services available to its citizens in the past decades. In the water supply sector, the Millennium Development Goal (MDG) targets have either already been met (notably in the rural water sector) or coverage is significant. In the sanitation sector, the achievements are less impressive, highlighting it as a neglected sector. There has also been steady progress in the development of policy frameworks, using national policies and guidelines as a touchstone. However, while prima facie progress would appear to be solid, the study reveals that, in fact, achievements are fragile, and serious structural issues threaten to undermine progress in the sector. Further, the quality of service is assessed as poor, with limited recourse for customers. Institutional fragmentation, piecemeal and heavily politicized planning efforts with little cohesion, and heavy and misdirected subsidies mark the sector, and negate sustainability. Evidence indicates that the gains of the past decades are likely to be reversed, and MDG targets will in fact not be met, should these issues not be addressed as a matter of urgency. As Pakistan and Punjab province move towards newly elected governments, there is an opportunity for spearheading reform. The 18th Constitutional Amendment has already given the province control of the sector. An important water Act lies on the anvil and passing this could put in place the framework for developing a coherent sector-wide approach, and provide legal impetus for the creation of a regulatory authority. This will be an important starting point for addressing the structural flaws, which currently beset the sector. This Service Delivery Assessment (SDA) has been produced in collaboration with the Government of Punjab and other stakeholders.